PREVALENCE OF Entamoeba histolytica/Entamoeba dispar IN THE CITY OF CAMPINA GRANDE, IN NORTHEASTERN BRAZIL - Silva, Maria Teresa Nascimento; Santana, José Valfrido; Bragagnoli, Gérson; Marinho, Alexandre Magno da Nóbrega; Malagueño, Elizabeth (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
There is a clear need to perform epidemiological studies to find the true prevalence of Entamoeba histolytica around the world. The evaluation of this prevalence has been hindered by the existence of two different species which are morphologically identical, but genetically different, namely E. histolytica, which causes amebiasis, and E. dispar, which is non-pathogenic. In Brazil, the E. dispar has been detected in communities in the Southeastern (SE) and Northeastern (NE) regions with poor sanitation. However, individuals infected with E. histolytica have been identified in other regions. There is an absence of reports on the prevalence of these parasites in the state of Paraíba, which also has areas with poor sanitary conditions where a high prevalence of the E. histolytica/E. dispar complex has been detected in children from urban slums. The present study evaluated the prevalence of E. histolytica and E. dispar in 1,195 asymptomatic children between two and 10 years of age, living in a sprawling urban slum in Campina Grande, in the state of Paraíba, in Northeastern Brazil. These children were examined and their feces samples were analyzed microscopically. A total of 553 children tested positive for the E. histolytica/E. dispar complex, and 456 of the positive samples were tested with the E. histolytica II® ELISA kit. All 456 samples were negative for the presence of the adhesin E. histolytica specific antigen. The evidence suggests that in this community E. histolytica is absent and E. dispar is the dominant species.